MENJAGA KESATUAN DALAM PERBEDAAN: STUDI ATAS HADIS 73 GOLONGAN DAN IMPLIKASINYA DALAM KEHIDUPAN KONTEMPORER - Ali Yusuf Muzakki; M. Farid Zaini (Yayasan Haiah Nusratul Islam, 2026)
This study explores the fiqh-based interpretation of the well-known hadith concerning the division of the Muslim ummah into 73 sects, in which only one is deemed